The Effect of Character Values Integration in Teaching Learning Process on Student Behavior in Social Studies Class (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to find out the effect of character values integration in teaching learning process on student behavior in social studies class. The sample group involved 396 students of grade 4 to 6 at elementary schools in the province of Jakarta.  The data collected with the questionnaires were analysed with the structural equation model (SEM).  The results found that character values integration in teaching learning process through integrating character values in the beginning, core, and closing of learning activities in social studies class had predictive effects on student behavior described by student achievement, motivational, and social-emotional behavior in social studies class.. This research contributes practically by presenting that elementary schools can improve integration of character values in the context of teaching learning process to enhance the level of student behavior by providing a model for student behavior in social studies class.